Predicting 90-day prognosis for patients with stroke: a machine learning approach - Abujaber, Ahmad A.; Alkhawaldeh, Ibraheem M.; Imam, Yahia; Nashwan, Abdulqadir J.; Akhtar, Naveed; Own, Ahmed; Tarawneh, Ahmad S.; Hassanat, Ahmad B. (Frontiers in Neurology, 2023)
Background Stroke is a significant global health burden and ranks as the second leading cause of death worldwide. Objective This study aims to develop and evaluate a machine learning-based predictive tool for forecasting the 90-day prognosis of stroke patients after discharge as measured by the modified Rankin Score. Methods The study utilized data from a large national multiethnic stroke registry comprising 15,859 adult patients diagnosed with ischemic or hemorrhagic stroke. Of these, 7,452 patients satisfied the study’s inclusion criteria. Feature selection was performed using the correlation and permutation importance methods. Six classifiers, including Random Forest (RF), Classification and Regression Tree, Linear Discriminant Analysis, Support Vector Machine, and k-Nearest Neighbors, were employed for prediction. Results The RF model demonstrated superior performance, achieving the highest accuracy (0.823) and excellent discrimination power (AUC 0.893). Notably, stroke type, hospital acquired infections, admission location, and hospital length of stay emerged as the top-ranked predictors. Conclusion The RF model shows promise in predicting stroke prognosis, enabling personalized care plans and enhanced preventive measures for stroke patients. Prospective validation is essential to assess its real-world clinical performance and ensure successful implementation across diverse healthcare settings.